KONVERGENSI NILAI ADAT SEBAGAI JURAL POSTULATE DENGAN TUJUAN PIDANA DALAM RUUHUKUM PIDANA (Studi Socio-Legal Sumpah Banyu Roto di Masyrakat Hukum Tengger) - Febriansyah Ramadhan; Muhammad Rizal Dwi Kuncoro (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2018)
The legal identify in the original version of Indonesia has been camouflaged by the hegemony of the Western legal opinion that tends to be legalistic and formalistic in nature and to have liberal spirits. At present, the legal society is stunned by the phenomenon that they should accept a modern law that as if it has been fallen from the sky. Law is the crystallization of the society‟s morality, values, and identity. Law is values that are born from the earth the people step on, therefore, it does not suddenly fall from the sky and should be accepted by all levels of society. It is high time to purify the national legal identity by placing the customary law and its layers of instruments as a value that will influence the content of the positive law. The Banyu Roto‟s pledge, as a value and customary law prevailed among the Tengger tribe, is the value and norm serving as the daily life guidance in order to maintain the balance of the Tengger society. Therefore, a national criminal reform with an orientation to maintain and restore the condition and order may be made. This present article will try to answer the 2 following questions: first, what is the meeting point/convergence between Banyu Roto‟s Pledge as a jural postulate and the aim of the Crime in the revision of the Criminal Law in the future? Second, what is the way of life (the value of the people in Tengger tribe) dealing with the basic value contained in the Banyu Roto‟s pledge used to see the criminalization of adultery outside marriage in Indonesia? A socio-legal research method was employed in this present research.